Tinjauan Kejadian Misfiled di Rak Penyimpanan Rekam Medis RSUD Dr. Adjidarmo Kab. Lebak Tahun 2022 - Nabila Raihani; Wiwik Viatiningsih; Noor Yulia; Deasy Rosmala Dewi (Jurnal Ilmiah Perekam dan Informasi Kesehatan Imelda, 2023)
Misfiled is an error in the storage of medical records, or the non-discovery of medical records on the storage shelf. This study aims to determine the description of misfiled events in the medical record storage shelf of RSUD Dr. Adjidarmo Kab. Lebak in 2022. This study uses a descriptive analysis method with a quantitative approach by conducting observations and interviews. The results of the study with 99 samples found that 9 (9.1%) of the misfiled and the non-misfiled were 90 (90,9%). Most of the medical records that occurred were misfiled because it did not fit on the proper shelf or medical record documents located on another shelf. The storage system used is a centralized system and its alignment system uses a digit filing terminal. The first factor causing the misfiled in the hospital is that the medical record officer is not careful in storing medical records, because there are still often errors when reading the numbers written. Another factor is in the facilities and infrastructure of the storage room, because there is no tracer as a substitute for medical records that come out of the shelves. The advice is always to use tracers to replace medical records that come out, so as not to misfiled the alignment of medical records.